CPCR Results in Cardiac Arrested Patients in Motahari Hospital Affiliated to Jahrom University of Medical Sciences, Iran, 2011-2015 - Mohsen Hojat (Journal of Global Pharma Technology, 2017)
Introduction Cardiopulmonary resuscitation (CPR) in hospital has received much attention over the last decade. Computing international indices of CPR in hospital can be a guideline for researchers and managers in determining the executive and research priorities. So this study was designed and implemented to evaluate the results of CPR in Motahari Hospital in Jahrom. Materials and Methods this study was a cross-sectional and analytic study that designed and implemented in Motahari Hospital affiliated with the Jahrom University of Medical Sciences during 2011-2015. All patients receiving resuscitation were evaluated each year and in each section as the census regardless of the background factors; and information was collected through cardiopulmonary resuscitation checklist which was filled by clinical supervisor and hospital resident doctor per shift. Content and face validity was calculated according to opinion of 5 professors, content validity index (0.77), and the content validity ratio (0.83); reliability of the tool was calculated through education of clinical supervisors and acquisition of Kappa coefficient to researchers (96%). Data were analyzed by SPSS16 software. Results In this study, resuscitation was annually performed on 353 patients from 389 cases during 2011-2015, that the patients were 78.61% males and 21.39% females with an age range of 1-98 years and an average age of 55.6 years. Of the total cases conducted resuscitation, successful resuscitation was 56.29% at 24 hours and return of spontaneous blood circulation was 63.03% at first 20 minutes. Average total of duration of resuscitation was reported 59.58 minutes. Conclusion the results of this study are consistent with the results of European and America countries. It also shows that the faster resuscitation start and quick and correct use of defibrillator can improve short-term and long-term indicators of resuscitation.Keywords: Cardiopulmonary resuscitation (CPR), ROSC - S to D.